Multi-layer high-strength waterproof composite paperboard and preparation method thereof
By applying a mixed coating of polyurethane resin, acrylic resin, modified silica and modified microfibrillated cellulose on the cardboard substrate, the perfluoroalkyl group polymer used in the manufacturing process of existing waterproof paperboard materials has strong bioaccumulative properties and difficulty in degradation, and a high-strength, low-cost and environmentally friendly waterproof paperboard material is achieved.
Patent Information
- Application Number
- CN202310771793.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The perfluoroalkyl group polymers used in the manufacturing process of existing waterproof cardboard materials have problems such as strong bioaccumulation and difficulty in degradation, and the preparation process is complex and costly, which affects the environment and human safety.
Multi-layer high-strength waterproof composite cardboard is used to mix polyurethane resin emulsion, acrylic resin emulsion, modified silica, mixed particles, additives and deionized water in a specific proportion to form a coating and apply it on the cardboard substrate. The waterproof performance and mechanical properties of the cardboard are improved by the combination of modified silica and modified microfibrillated cellulose.
It realizes composite cardboard with impermeable water and good mechanical properties, reduces preparation costs, and improves the waterproof performance and strength of cardboard, ensuring human safety and environmental protection performance.
Smart Images

Figure GHA0000009554850000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of paperboard coatings and relates to a multi-layer high-strength waterproof composite paperboard and a preparation method thereof. Background Art
[0002] During the production process of many paperboard materials, a very small amount of waterproofing agent is added or a layer of waterproof coating is applied on the surface of the paper to reduce the surface tension of the paper, which can give the paper substrate waterproof properties without affecting the recycling of paper products. Although the waterproofing effect is excellent, this type of waterproofing agent is usually a polymer containing a perfluoroalkyl group, and its manufacturing technical conditions are relatively harsh, the preparation process is relatively complex, and the material preparation cost is high. In addition, the polymer of the perfluoroalkyl group has the defects of strong bioaccumulation and difficulty in degradation, especially long-term contact with food. After the food is consumed, it is highly toxic to the human body. In addition, the paperboard is difficult to recycle and has a potential pollution effect on the environment. Summary of the invention
[0003] The object of the present invention is to provide a multi-layer high-strength waterproof composite paperboard and a preparation method thereof, which has the characteristics of being impermeable, having good mechanical properties and being low in cost.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A multi-layer high-strength waterproof composite paperboard, comprising a paperboard substrate and at least one layer of coating applied on the paperboard substrate, wherein the coating comprises the following components by weight: 30-50 parts of polyurethane resin emulsion, 20-30 parts of acrylic resin emulsion, 10-15 parts of modified silicon dioxide, 5-8 parts of mixed particles, 3-5 parts of additives and 20-30 parts of deionized water.
[0006] The present invention also discloses a method for preparing modified silicon dioxide, comprising the following steps:
[0007] 1) Add straight-chain olefin and catalyst into a reactor, stir and mix, heat to 100-150°C, add triethoxysilane, maintain the temperature and stir for 10-36h, filter out the catalyst, and obtain a mixed solution;
[0008] 2) After adding anhydrous ethanol, stir and mix for 5-15 minutes, add ammonia water, stir and react for 2-8 hours, cool to room temperature, wash with anhydrous ethanol 2-3 times, and vacuum dry to obtain modified silica.
[0009] The usage ratio of the linear olefin, triethoxysilane, catalyst, anhydrous ethanol and ammonia water is 9-12g: 16-22g: 0.5-0.8g: 400-500ml: 25-30mL, and the concentration of the ammonia water is 25-30%.
[0010] As a preferred technical solution of the present invention, the linear olefin is a linear olefin with 9-12 carbon atoms, and the linear olefin is one or more of n-nonene, n-decene, 1-undecene or 1-dodecene; the catalyst is one or more of iron, cobalt, nickel, aluminum or magnesium metal catalysts. As a preferred technical solution of the present invention, the additive is etherified starch and hydroxypropyl methylcellulose, and the weight ratio of the etherified starch and hydroxypropyl methylcellulose is 2-3:1-1.2; wherein the etherified starch can be commercially available, such as Qinyang Xinxing Chemical Co., Ltd., model YLS-2; the hydroxypropyl methylcellulose can be commercially available, such as Sigma-Aldrich (Shanghai) Trading Co., Ltd., CAS No. 9004-65-3.
[0011] As a preferred technical solution of the present invention, the mixed particles are composed of modified microfibrillated cellulose of three different aspect ratios, the aspect ratio is 2:3:5, and the mass ratio is 2:3:7; the present invention also discloses a method for preparing the modified microfibrillated cellulose, comprising the following steps: soaking in sodium hydroxide solution for 30 minutes and then drying at 100°C.
[0012] Furthermore, a method for preparing a multi-layer high-strength waterproof composite paperboard is provided, characterized in that the preparation method comprises the following steps:
[0013] (1) adding modified silica and mixed particles to deionized water, heating and then keeping the temperature to obtain an emulsion for use;
[0014] (2) Adding polyurethane resin emulsion, acrylic resin emulsion and additives to the emulsion in sequence while stirring, dispersing at high speed to obtain a coating, applying the coating to a paperboard substrate and curing it to obtain a composite paperboard.
[0015] As a preferred technical solution of the present invention, in step (1), the heating temperature is 80-90°C and the insulation time is 20-30 minutes.
[0016] As a preferred technical solution of the present invention, in step (2), the stirring speed is 500-700 r / min; the high-speed dispersion condition is high-speed dispersion at 10,000 rpm for 3-5 min.
[0017] Beneficial effects of the present invention:
[0018] 1. The scheme of the present invention directly generates modified silica by forming Si-O-Si covalent bonds with low surface energy substances; the combination of the two generates silica particles with different particle sizes by introducing long carbon chains, thereby increasing the surface roughness of the modified silica particles; the micron structure and roughness of the modified silica particles cause gaps to be generated when water contacts the modified silica particles to store air and act as a buffer area, thereby reducing the contact area between water and the modified silica, and ultimately improving the waterproof performance of the composite paperboard.
[0019] 2. Modified microfibrillated cellulose can interact with polyurethane resin and acrylic resin. By modifying the modified microfibrillated cellulose, the water resistance of the composite paperboard is increased. Three modified microfibrillated celluloses with different aspect ratios are selected and their ratios are adjusted to improve the surface roughness of the modified microfibrillated cellulose and increase the number of oxygen-containing functional groups on the surface of the modified microfibrillated cellulose. This increases the surface polarity of the modified microfibrillated cellulose, thereby improving the interfacial bonding strength between the modified microfibrillated cellulose and the paperboard substrate after fusion with the polyurethane resin and acrylic resin, thereby greatly improving the strength of the composite paperboard. DETAILED DESCRIPTION
[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0021] In the scheme of the present invention, the mixed particles used are composed of three modified microfibrillated celluloses with different aspect ratios, the aspect ratio is 2:3:5, and the mass ratio is 2:3:7; the modified microfibrillated cellulose is prepared by soaking in sodium hydroxide solution for 30 minutes and then drying at 100°C. The three modified microfibrillated celluloses with different aspect ratios are evenly mixed to obtain mixed particles.
[0022] Example 1
[0023] The coating comprises the following components by weight: 30 parts of polyurethane resin emulsion, 20 parts of acrylic resin emulsion, 10 parts of modified silicon dioxide, 5 parts of mixed particles, 3 parts of additives and 20 parts of deionized water;
[0024] The additives are etherified starch and hydroxypropyl methylcellulose, and the weight ratio of the etherified starch to the hydroxypropyl methylcellulose is 2:1;
[0025] The preparation method of the modified silicon dioxide comprises the following steps:
[0026] 1) n-nonene and iron are added to a reactor, stirred and mixed, heated to 100° C., triethoxysilane is added, the temperature is maintained and stirred for 10 hours, and the iron is filtered off to obtain a mixed solution;
[0027] 2) After adding anhydrous ethanol, stirring and mixing for 5 minutes, adding ammonia water, stirring and reacting for 2 hours, cooling to room temperature, washing with anhydrous ethanol twice, and vacuum drying to obtain modified silica.
[0028] The dosage ratio of n-nonene, triethoxysilane, iron, anhydrous ethanol and ammonia water is 9g:16g:0.5g:400ml:25mL, and the concentration of ammonia water is 25%.
[0029] In the scheme of the present invention, the method for preparing the composite paperboard comprises the following steps:
[0030] (1) adding modified silica and mixed particles to deionized water, heating to 80° C. and then keeping the temperature for 20 minutes to obtain an emulsion for use;
[0031] (2) Adding polyurethane resin emulsion, acrylic resin emulsion, etherified starch and hydroxypropyl methylcellulose to the emulsion in sequence while stirring, and dispersing at high speed to obtain a coating, and applying the coating to a paperboard substrate and curing to obtain a composite paperboard, wherein the stirring speed is 500 r / min; and the high-speed dispersion condition is high-speed dispersion at 10,000 rpm for 3 min.
[0032] Example 2
[0033] The coating comprises the following components by weight: 40 parts of polyurethane resin emulsion, 25 parts of acrylic resin emulsion, 12.5 parts of modified silicon dioxide, 6.5 parts of mixed particles, 4 parts of additives and 25 parts of deionized water;
[0034] The additives are etherified starch and hydroxypropyl methylcellulose, and the weight ratio of the etherified starch to the hydroxypropyl methylcellulose is 2.5:1.1;
[0035] The preparation method of the modified silicon dioxide comprises the following steps:
[0036] 1) n-nonene and iron are added to a reactor, stirred and mixed, heated to 125° C., triethoxysilane is added, the temperature is maintained and stirred for 23 hours, and the iron is filtered off to obtain a mixed solution;
[0037] 2) After adding anhydrous ethanol, stir and mix for 10 minutes, add ammonia water, stir and react for 5 hours, cool to room temperature, wash twice with anhydrous ethanol, and vacuum dry to obtain modified silica.
[0038] The dosage ratio of n-nonene, triethoxysilane, iron, anhydrous ethanol and ammonia water is 10.5 g: 19 g: 0.65 g: 450 ml: 27.5 mL, and the concentration of ammonia water is 27.5%.
[0039] In the scheme of the present invention, the method for preparing the composite paperboard comprises the following steps:
[0040] (1) adding modified silica and mixed particles to deionized water, heating to 85° C. and then keeping the temperature for 25 minutes to obtain an emulsion for use;
[0041] (2) Adding polyurethane resin emulsion, acrylic resin emulsion, etherified starch and hydroxypropyl methylcellulose to the emulsion in sequence while stirring, and dispersing at high speed to obtain a coating, and applying the coating to a paperboard substrate and curing to obtain a composite paperboard, wherein the stirring speed is 600 r / min; and the high-speed dispersion condition is high-speed dispersion at 10,000 rpm for 4 min.
[0042] Example 3
[0043] The coating comprises the following components by weight: 50 parts of polyurethane resin emulsion, 30 parts of acrylic resin emulsion, 15 parts of modified silicon dioxide, 8 parts of mixed particles, 5 parts of additives and 30 parts of deionized water;
[0044] The additives are etherified starch and hydroxypropyl methylcellulose, and the weight ratio of the etherified starch to the hydroxypropyl methylcellulose is 3:1.2;
[0045] The preparation method of the modified silicon dioxide comprises the following steps:
[0046] 1) n-nonene and iron are added to a reactor, stirred and mixed, and then heated to 150° C., triethoxysilane is added, the temperature is maintained and stirred for 36 hours, and the iron is filtered off to obtain a mixed solution;
[0047] 2) After adding anhydrous ethanol, stirring and mixing for 15 minutes, adding ammonia water, stirring and reacting for 8 hours, cooling to room temperature, washing with anhydrous ethanol for 3 times, and vacuum drying to obtain modified silica.
[0048] The dosage ratio of n-nonene, triethoxysilane, iron, anhydrous ethanol and ammonia water is 12g:22g:0.8g:500ml:30mL, and the concentration of ammonia water is 30%.
[0049] In the scheme of the present invention, the method for preparing the composite paperboard comprises the following steps:
[0050] (1) adding modified silica and mixed particles to deionized water, heating to 90° C. and then keeping the temperature for 30 minutes to obtain an emulsion for use;
[0051] (2) Adding polyurethane resin emulsion, acrylic resin emulsion, etherified starch and hydroxypropyl methylcellulose to the emulsion in sequence while stirring, and dispersing at high speed to obtain a coating, and applying the coating to a paperboard substrate and curing to obtain a composite paperboard, wherein the stirring speed is 700 r / min; and the high-speed dispersion condition is high-speed dispersion at 10,000 rpm for 5 min.
[0052] Example 4
[0053] Compared with Example 2, the difference is that the straight-chain olefin is n-nonene, and the other components, preparation steps and parameters are the same.
[0054] Example 5
[0055] Compared with Example 2, the difference is that the straight-chain olefin is n-decene, and the other components, preparation steps and parameters are the same.
[0056] Example 6
[0057] Compared with Example 2, the difference is that the straight-chain olefin is 1-undecene, and the other components, preparation steps and parameters are the same.
[0058] Example 7
[0059] Compared with Example 2, the difference is that the straight-chain olefin is 1-dodecene, and the other components, preparation steps and parameters are the same.
[0060] Example 8
[0061] Compared with Example 2, the difference is that 13 parts of modified silicon dioxide are used, and the other components, preparation steps and parameters are the same.
[0062] Example 9
[0063] Compared with Example 2, the difference is that 14 parts of modified silicon dioxide are used, and the other components, preparation steps and parameters are the same.
[0064] Example 10
[0065] Compared with Example 2, the difference is that 15 parts of modified silicon dioxide are used, and the other components, preparation steps and parameters are the same.
[0066] Comparative Example 1
[0067] Compared with Example 2, the difference is that the straight-chain olefin is n-propylene, and the other components, preparation steps and parameters are the same.
[0068] Comparative Example 2
[0069] Compared with Example 2, the difference is that the straight-chain olefin is n-pentene, and the other components, preparation steps and parameters are the same.
[0070] Comparative Example 3
[0071] Compared with Example 2, the difference is that 12.5 parts of silicon dioxide are used, and the other components, preparation steps and parameters are the same.
[0072] Comparative Example 4
[0073] Compared with Example 2, the difference is that 15 parts of silicon dioxide are used, and the other components, preparation steps and parameters are the same.
[0074] Comparative Example 5
[0075] Compared with Example 2, the difference is that 2 parts of modified silicon dioxide are used, and the other components, preparation steps and parameters are the same.
[0076] Comparative Example 6
[0077] Compared with Example 2, the difference is that the mixed particles are composed of three modified microfibrillated celluloses with different aspect ratios, the aspect ratio is 1:3:5, the mass ratio is 1:3:7, and the other components, preparation steps and parameters are the same.
[0078] Comparative Example 7
[0079] Compared with Example 2, the difference is that the mixed particles are composed of three modified microfibrillated celluloses with different aspect ratios, the aspect ratio is 3:3:5, the mass ratio is 3:3:7, and the other components, preparation steps and parameters are the same.
[0080] Comparative Example 8
[0081] Compared with Example 2, the difference is that the mixed particles are composed of two modified microfibrillated celluloses with different aspect ratios, the aspect ratio is 2:3, the mass ratio is 2:3, and the other components, preparation steps and parameters are the same.
[0082] Comparative Example 9
[0083] Compared with Example 2, the difference is that the mixed particles are composed of two modified microfibrillated celluloses with different aspect ratios, the aspect ratio is 3:5, and the mass ratio is 3:7, and the other components, preparation steps and parameters are the same.
[0084] Comparative Example 10
[0085] Compared with Example 2, the difference is that the mixed particles are composed of three types of microfibrillated cellulose with different aspect ratios, the aspect ratio is 2:3:5, and the mass ratio is 2:3:7, that is, the three types of microfibrillated cellulose with different aspect ratios are not modified, and the other components, preparation steps and parameters are the same.
[0086] The composite paperboards obtained from Examples 1-10 and Comparative Examples 1-10 were subjected to the following two tests, respectively. The test results are shown in Table 1.
[0087] 1. Surface tension test:
[0088] The surface tension of the coating was determined according to GB / T22237 / 2008.
[0089] 2. Elongation at break test:
[0090] The elongation at break of the film sample was tested using an LLY-06E electronic single fiber strength tester. The tensile speed was set to 20 mm / min, the clamping distance was 10 mm, each sample was tested 20 times, and the results were averaged.
[0091] Table 1
[0092]
[0093]
[0094] From the test results in Table 1, it can be seen that compared with comparative examples 1-10, the waterproof performance and mechanical properties of the composite paperboard prepared by the embodiment 1-10 of the present invention are significantly improved. The composite paperboard of the present invention is waterproof and has high strength, high safety to the human body, and low recycling cost.
[0095] Compared with Comparative Examples 1-5, Examples 1-10 show that the low surface energy substance directly generates modified silica by forming Si-O-Si covalent bonds. The combination of the two produces silica particles of different particle sizes by introducing long carbon chains, thereby increasing the surface roughness of the modified silica particles. The micron structure and roughness of the modified silica particles cause gaps to be generated when water contacts the modified silica particles to store air and act as a buffer area, thereby reducing the contact area between water and the modified silica, and ultimately improving the waterproof performance of the composite paperboard.
[0096] Compared with comparative examples 6-10, examples 1-10 show that the modified microfibrillated cellulose and the polyurethane resin and the acrylic resin can interact with each other. By modifying the modified microfibrillated cellulose, the water resistance of the composite paperboard is increased. Three modified microfibrillated celluloses with different aspect ratios are selected and their proportions are adjusted to increase the surface roughness of the modified microfibrillated cellulose and the number of oxygen-containing functional groups on the surface of the modified microfibrillated cellulose, thereby increasing the surface polarity of the modified microfibrillated cellulose. This improves the interfacial bonding strength between the modified microfibrillated cellulose and the paperboard substrate after being fused with the polyurethane resin and the acrylic resin, thereby greatly improving the strength of the composite paperboard.
[0097] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A multi-layer high-strength waterproof composite paperboard, comprising a paperboard substrate and at least one layer of coating applied on the paperboard substrate, characterized in that: The coating comprises the following components by weight: 30-50 parts of polyurethane resin emulsion, 20-30 parts of acrylic resin emulsion, 10-15 parts of modified silicon dioxide, 5-8 parts of mixed particles, 3-5 parts of additives and 20-30 parts of deionized water; The preparation method of the modified silicon dioxide comprises the following steps: 1) Add straight-chain olefin and catalyst into the reactor, stir and mix, heat to 100-150°C, add triethoxysilane, maintain the temperature and stir for 10-36h, filter out the catalyst, and obtain a mixed solution; 2) After adding anhydrous ethanol, stir and mix for 5-15 minutes, add ammonia water, stir and react for 2-8 hours, cool to room temperature, wash with anhydrous ethanol 2-3 times, and vacuum dry to obtain modified silica; The linear olefin is a linear olefin having 9 to 12 carbon atoms, and the linear olefin is one or more of n-nonene, n-decene, 1-undecene or 1-dodecene; The mixed particles are composed of three modified microfibrillated celluloses with different aspect ratios, the aspect ratio is 2:3:5, and the mass ratio is 2:3:7; the modified microfibrillated cellulose is prepared by soaking in a sodium hydroxide solution for 30 minutes and then drying at 100°C.
2. The multi-layer high-strength waterproof composite paperboard according to claim 1, characterized in that: The usage ratio of the linear olefin, triethoxysilane, catalyst, anhydrous ethanol and ammonia water is 9-12g:16-22g:0.5-0.8g:400-500ml:25-30mL, and the concentration of the ammonia water is 25-30%.
3. The multi-layer high-strength waterproof composite paperboard according to claim 1, characterized in that: The catalyst is one or more of iron, cobalt, nickel, aluminum or magnesium metal catalysts.
4. The multi-layer high-strength waterproof composite paperboard according to claim 1, characterized in that: The additives are etherified starch and hydroxypropyl methylcellulose, and the weight ratio of the etherified starch to the hydroxypropyl methylcellulose is 2-3:1-1.
2.
5. A method for preparing a multi-layer high-strength waterproof composite paperboard according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Adding modified silica and mixed particles to deionized water, heating and then keeping the temperature to obtain an emulsion for use; (2) Adding polyurethane resin emulsion, acrylic resin emulsion and additives to the emulsion in sequence while stirring, dispersing at high speed to obtain a coating, applying the coating to a paperboard substrate and curing it to obtain a composite paperboard.
6. The method for preparing a multi-layer high-strength waterproof composite paperboard according to claim 5, characterized in that: In step (1), the heating temperature is 80-90°C and the insulation time is 20-30 minutes.
7. The method for preparing a multi-layer high-strength waterproof composite paperboard according to claim 5, characterized in that: In step (2), the stirring speed is 500-700 r / min; the high-speed dispersion condition is high-speed dispersion at 10,000 rpm for 3-5 min.
Citation Information
Patent Citations
Corrugated case with high moisture-proof performance and strong anti-osmosis property
CN109853290A